Microsoft 70-341 : core solutions of Exchange Server 2013 - Parisi, Ralph; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The new Exchange Server 2013 Core Solutions course provides full coverage of the knowledge and skills to plan, deploy, secure, support and manage Exchange Server 2013. This new and exciting course will enable you to configure Exchange Server 2013 and provide the information needed to maintain, troubleshoot and monitor Exchange Server 2013. This new Exchange 2013 course provides you the needed training to optimize performance, minimize errors and security threats in Exchange Server 2013, as well as highlighting the considerations, guidelines, best practices and more. This course brings together all the features of using Exchange Server 2013."--Resource description page.
Presenter, Ralph Parisi.
Title and publication information from resource description page (Safari, viewed March 17, 2017).
Keywords: Microsoft Exchange server; Electronic books